2020
DOI: 10.1038/s41598-020-68217-6
|View full text |Cite
|
Sign up to set email alerts
|

Women’s socioeconomic position in ontogeny is associated with improved immune function and lower stress, but not with height

Abstract: immune function, height and resource accumulation comprise important life history traits in humans. Resource availability models arising from life history theory suggest that socioeconomic conditions influence immune function, growth and health status. In this study, we tested whether there are associations between family income during ontogeny, adult height, cortisol level and immune response in women. A hepatitis B vaccine was administered to 66 young Latvian women from different socioeconomic backgrounds, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 106 publications
(174 reference statements)
0
10
1
Order By: Relevance
“…Correlations between height and income per family member were roughly similar among boys and girls (boys: r s = 0.19; girls: r s = 0.14). This result differs from findings of two studies performed in Latvia in 2010 where income per family member correlated positively with height in boys ( Krams et al, 2019 ) but not in girls ( Rubika et al, 2020 ). However, we found that cranial volume was more strongly associated with income among boys ( r s = 0.18) than among girls ( r s = 0.08).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Correlations between height and income per family member were roughly similar among boys and girls (boys: r s = 0.19; girls: r s = 0.14). This result differs from findings of two studies performed in Latvia in 2010 where income per family member correlated positively with height in boys ( Krams et al, 2019 ) but not in girls ( Rubika et al, 2020 ). However, we found that cranial volume was more strongly associated with income among boys ( r s = 0.18) than among girls ( r s = 0.08).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, we asked whether different growth constraints affect boys and girls in a similar manner in the light of an idea that males are less buffered against the environmental effects on growth and development ( Stinson, 1985 ). For instance, studies in Latvia in the period following economic transition at the end of twentieth century have reported that material resource shortage at infancy relates to the height of men more strongly than to the height of women ( Krams et al, 2019 ; Rubika et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study on a similar population of women as the Latvian male sample of Krams et al (2019), however, found that women's height was not predicted by their family income during development, even though immune function was (Rubika et al, 2020). It is thus possible that the development and expression of male height are condition-dependent in a similar way to many other sexually selected traits, therefore being more sensitive to resource availability than female height (Krams et al, 2019;Rubika et al, 2020). Overall, height can be useful as a cue of good genes, better immunity, higher intelligence, and more resource-rich developmental environments in men (Marioni et al, 2014;Krams et al, 2019), making male height an important cue for women for a number of different reasons.…”
Section: Heightmentioning
confidence: 94%
“…Higher family socioeconomic status during development predicts both greater height and improved immune function in adult men, suggesting that these traits cluster towards the slow end of the life history spectrum (Krams et al, 2019). A study on a similar population of women as the Latvian male sample of Krams et al (2019), however, found that women's height was not predicted by their family income during development, even though immune function was (Rubika et al, 2020). It is thus possible that the development and expression of male height are condition-dependent in a similar way to many other sexually selected traits, therefore being more sensitive to resource availability than female height (Krams et al, 2019;Rubika et al, 2020).…”
Section: Heightmentioning
confidence: 99%
“…Each organism's life history can be summarized as a cumulative series of energyallocation decisions that operate within the finite energy budgets available to each organism; as such, these energy-allocation decisions are represented by a suite of developmental, physiological, psychological, behavioral, and reproductive traits (Krams et al, 2019;Luoto, 2019;Rubika et al, 2020;Wells & Stock, 2020). Life history strategies encompass body growth (how fast and large to grow), how to address risks and defend against threats, and how to schedule reproductive effort, including the number of offspring and the investment allocated to each offspring, which curtails energy budgets available to other activities (Ellison, 2017;Krams et al, 2019;Wells & Stock, 2020;Worthman & Trang, 2018).…”
Section: Hormonally Mediated Fast Life History Strategymentioning
confidence: 99%